Errors Middle School Students Make When Performing Mathematical Modelling Tasks - Porras Lizano, Karen (2021)
Background: In Costa Rica, since 2012, schoolchildren have been trained in modelling as a fundamental part of the educational curriculum. Objectives: To identify and characterise errors incurred by a group of secondary school students in Costa Rica when applying the mathematical modelling process phases when solving direct proportionality tasks. Design: Through a qualitative approach, specifically a case study, it aims to study the participants’ social interpretations. Setting and Participants: The modelling tasks were applied to 24 students attending the 7th level of middle school education in the province of San José in Costa Rica, when the topic of direct proportionality is deepened and the participants have been instructed in modelling tasks since the first years of elementary school. Data collection and analysis: Information was collected through participants’ written productions, researchers’ observation, and interviews. Content analysis was carried out through the categorisation proposed by Abrate et al. (2006) to analyse mathematical errors. Results: The participants did not apply all phases of the mathematical modelling process, making more errors due to incorrect or unintended calculations and incorrect associations when solving the mathematical model. Conclusions: We concluded that the errors detected in this work are elements of reflection, progress, and feedback that should encourage the teachers’ search for strategies that help solve the deficiencies that emerge when students solve modelling activities.